2021
DOI: 10.1186/s12934-021-01680-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the T7 RNA polymerase expression in E. coli BL21 (DE3) to provide more host options for recombinant protein production

Abstract: Escherichia coli is the most widely used bacterium in prokaryotic expression system for the production of recombinant proteins. In BL21 (DE3), the gene encoding the T7 RNA polymerase (T7 RNAP) is under control of the strong lacUV5 promoter (PlacUV5), which is leakier and more active than wild-type lac promoter (PlacWT) under certain growth conditions. These characteristics are not advantageous for the production of those recombinant proteins with toxic or growth-burdened. On the one hand, leakage expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 34 publications
1
19
0
10
Order By: Relevance
“…Du et al replaced P lacUV5 with a rhamnose promoter (P rhaBAD ), arabinose promoter (P araBAD ), and tetracycline promoter (P tet ) in BL21(DE3) to optimise the production of recombinant proteins by regulating the transcription and leakage of T7 RNAP. These engineered strains have been successfully used to improve the production of membrane proteins, including cytosine transporter protein (CodB), membrane protein foldase (YidC), and F-ATPase subunit b (Ecb) [ 27 ]. Roosild et al discovered that Mistic, an unusual B. subtilis integral membrane protein, folds autonomously into the membrane—bypassing the cellular translocation machinery—and can be used as a fusion tag for the heterologous expression of eukaryotic membrane proteins in their native form in E. coli [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Du et al replaced P lacUV5 with a rhamnose promoter (P rhaBAD ), arabinose promoter (P araBAD ), and tetracycline promoter (P tet ) in BL21(DE3) to optimise the production of recombinant proteins by regulating the transcription and leakage of T7 RNAP. These engineered strains have been successfully used to improve the production of membrane proteins, including cytosine transporter protein (CodB), membrane protein foldase (YidC), and F-ATPase subunit b (Ecb) [ 27 ]. Roosild et al discovered that Mistic, an unusual B. subtilis integral membrane protein, folds autonomously into the membrane—bypassing the cellular translocation machinery—and can be used as a fusion tag for the heterologous expression of eukaryotic membrane proteins in their native form in E. coli [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This strategy not only regulates the allocation of resources between cell growth and protein production but also circumvents the disadvantages of using inducers, such as toxic side effects and leaky expression. This is a common strategy for membrane protein expression [ 27 ]. However, the expression of MenA in BS007 was the lowest, which may have been due to the short stationary period of B. subtilis .…”
Section: Resultsmentioning
confidence: 99%
“…Based on these observations, we propose that the ROK family regulator AraU and its downstream ABC transporter ( araFDH ) play a role in galactose (and potentially fructose) transport in B. longum NCC 2705. The activation pattern of P BL1694 shares several similarities to the arabinose inducible P BAD promoter that has been used to construct widely used sets of inducible expression vectors in E. coli 37 , 38 . Therefore, the P BL1694 promoter could represent an interesting option for the construction of a galactose-inducible gene expression system for B. longum NCC 2705 and possibly other bifidobacteria in which the regulation of the AraFDH transporter is conserved.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the membrane protein expression host C41(DE3) was obtained by stress screening, while the autolysin expression host BL21(DE3-lac1G) was constructed by recombining P lacUV5 with P lac sequences [10,20,31]. Furthermore, the P lacUV5 is independent of CRP, which makes it leakier than P lac [32]. Replacing the promoter of T7 RNAP with other kinds of inducible promoters is an effective way to regulate transcription levels and reduce leakage (Fig.…”
Section: Regulation Of the Target Protein Expression Rate-t7 Rnapmentioning
confidence: 99%
“…1B). Du et al [32] tested the effects of three inducible promoters (P araBAD , P rhaBAD and P tet ) on the transcriptional intensity and leaky expression of T7 RNAP, respectively. It was found that all three promoters were suitable for prolonged fermentation of toxic proteins, whereby P rhaBAD and P tet were able to regulate T7 RNAP transcription more rigorously, providing additional options for the expression of various RPs, especially toxic proteins.…”
Section: Regulation Of the Target Protein Expression Rate-t7 Rnapmentioning
confidence: 99%